2004
DOI: 10.1128/aem.70.6.3681-3686.2004
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Xylose Pathway in Saccharomyces cerevisiae

Abstract: The baker's yeast Saccharomyces cerevisiae is generally classified as a non-xylose-utilizing organism. We found that S. cerevisiae can grow on D-xylose when only the endogenous genes GRE3 (YHR104w), coding for a nonspecific aldose reductase, and XYL2 (YLR070c, ScXYL2), coding for a xylitol dehydrogenase (XDH), are overexpressed under endogenous promoters. In nontransformed S. cerevisiae strains, XDH activity was significantly higher in the presence of xylose, but xylose reductase (XR) activity was not affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
86
1
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 46 publications
3
86
1
4
Order By: Relevance
“…The latter genes were also upregulated in the DS69473-Y353C mutant strain (see Table S2 in the supplemental material). However, the upregulation of SOR1 could also be caused by the increased influx of D-xylose into the cell, since D-xylose induces the expression of SOR1 (36). This may also apply to SOR2.…”
Section: Discussionmentioning
confidence: 99%
“…The latter genes were also upregulated in the DS69473-Y353C mutant strain (see Table S2 in the supplemental material). However, the upregulation of SOR1 could also be caused by the increased influx of D-xylose into the cell, since D-xylose induces the expression of SOR1 (36). This may also apply to SOR2.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mutants of S. pombe have been isolated that grow on galactose and constitutively express their GAL pathways (33), suggesting that S. pombe may respond to a different induction signal. Similarly, S. cerevisiae, although not classified as a xylose-using yeast (2), has been shown to grow on xylose when endogenous genes are overexpressed (34). The ability of Y. lipolytica to grow on D-xylose varies among strains (2,14,15), and it may be that the D-xylose pathways of C. tanzawensis and other yeasts, which possess XYL gene homologs but do not grow on D-xylose in classical assays (2), are likewise rewired.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that over-expression of these native S. cerevisiae genes using endogenous promoters enabled a specific growth rate of 0.01 h -1 on d-xylose in shake flasks [64]. However, in these shake-flask cultures this engineered yeast strain converted d-xylose into xylitol with a yield of 55%.…”
Section: Native D-xylose-metabolising Enzymes In S Cerevisiaementioning
confidence: 99%
“…However, in these shake-flask cultures this engineered yeast strain converted d-xylose into xylitol with a yield of 55%. Under anaerobic conditions, precluding respiratory NAD + regeneration, the strain overexpressing the endogenous enzymes was unable to utilise d-xylose [64].…”
Section: Native D-xylose-metabolising Enzymes In S Cerevisiaementioning
confidence: 99%